Quantum dot composite and preparation method thereof, quantum dot diffusion plate and preparation method thereof, and light-emitting device

By using quantum dot composites in the backlight module, the problems of reduced life, low luminous luminousness, large usage and high cost in the prior art are solved, and higher light conversion efficiency and light output brightness are achieved, and the mode is reduced Group thickness and cost.

CN115851260BActive Publication Date: 2025-02-11SUZHOU XINGSHUO NANOTECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111126385.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-26
Publication Date
2025-02-11
Estimated Expiration
2041-09-26

AI Technical Summary

Technical Problem

The application of existing quantum dots in backlight modules has problems such as reduced lifetime, low luminous brightness, large usage and high cost, especially in use near the inlet and outgoing surfaces.

Method used

A quantum dot composite is adopted, including a solid shell and a liquid core. The liquid core contains quantum dots, photoinitiators and prepolymers. It is sprayed into the water phase through ultraviolet light irradiation and atomization device for photocuring to form a quantum dot composite .

Benefits of technology

The light conversion efficiency and light output brightness of the quantum dot composite are improved, the light conversion rate of the quantum dot diffusion plate is effectively improved, and the thickness and cost of the backlight module are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003278869250000011
    Figure HDA0003278869250000011
  • Figure HDA0003278869250000012
    Figure HDA0003278869250000012
  • Figure HDA0003278869250000013
    Figure HDA0003278869250000013
Patent Text Reader

Abstract

The present invention discloses a quantum dot composite and a preparation method thereof, a quantum dot diffusion plate and a preparation method thereof, and a light-emitting device. The quantum dot composite comprises a solid shell and a liquid core, wherein the liquid core comprises quantum dots, a photoinitiator, and a prepolymer, and the solid shell is formed by photocuring the liquid core. The solid shell is formed by photocuring the liquid core, and the light refractive index of the solid shell and the liquid core is inconsistent, so that the light conversion efficiency of the overall quantum dot composite is improved. The quantum dot composite is evenly dispersed in the main layer, which can effectively improve the light conversion rate and light output brightness of the obtained quantum dot diffusion plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of nanotechnology, and in particular relates to a quantum dot composite and a preparation method thereof, a quantum dot diffusion plate and a preparation method thereof, and a light-emitting device. Background Art

[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of (1-2)0nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum efficiency, high photochemical stability, not easy to photolyze, wide excitation, narrow emission, high color purity, and excellent optical properties such as fluorescence emission characteristics that can be adjusted by controlling the composition, particle size, and structure of quantum dots. They can make televisions have a high color gamut (NTSC) and have broad application prospects in the field of display technology.

[0003] The backlight module is the backlight component of the LCD display product, which is generally composed of a backlight source, a multi-layer backlight material and a supporting frame. The quality of the backlight determines important parameters such as the brightness, uniformity of the emitted light, and color gradation of the LCD screen, and largely determines the luminous effect of the LCD screen. The side-lit backlight module can be used with a light-emitting diode and a light guide plate, which has the advantage of being thinner. The light emitted by the LED package light source is coupled into the light guide plate, and is reflected and scattered by the reflector and the dots, and then propagates toward the LCD screen.

[0004] At present, the application of quantum dots in backlight modules mainly involves dispersing quantum dots in a medium and placing them near the light-entering surface or light-emitting surface of a light guide plate. However, if quantum dots are placed near the light-entering surface, they are easily affected by the temperature of the light source, which reduces their lifespan and results in low luminous brightness. If quantum dots are placed near the light-emitting surface, the amount of quantum dots used is large, the cost is high, and the module is thick.

[0005] Therefore, it is necessary to further optimize the application of quantum dots in backlight modules. Summary of the invention

[0006] In response to the above technical problems, the present application provides a quantum dot composite, comprising a solid shell and a liquid core containing a quantum dot glue liquid, wherein the quantum dot glue liquid and the liquid core contain quantum dots, a photoinitiator, and a prepolymer, and the solid shell is formed by photocuring the quantum dot glue liquid.

[0007] Furthermore, the particle size of the quantum dot complex is 0.1 to 1000 μm, and the inner diameter of the liquid core is 0.04 to 500 μm.

[0008] Furthermore, the prepolymer includes at least one of aliphatic polyurethane acrylate oligomer, aromatic polyurethane acrylate oligomer, epoxy oligomer, and polyester acrylate oligomer.

[0009] Furthermore, the liquid core contains the following components: the weight percentage of the quantum dots is 1-30wt%, the weight percentage of the photoinitiator is 0.1-10wt%, the weight percentage of the prepolymer is 10-80wt%, and the weight percentage of the monomer is 0-50wt%.

[0010] The present application also provides a method for preparing the quantum dot composite as described above, comprising the steps of:

[0011] S1, mixing quantum dots, photoinitiator, and prepolymer to form a quantum dot glue solution;

[0012] S2, adding the quantum dot glue solution into an aqueous phase with a pH value of 7 to 9, and irradiating with ultraviolet light to obtain the quantum dot complex.

[0013] Furthermore, step S2 includes: using an atomizing device to spray the quantum dot glue solution into the water phase.

[0014] Furthermore, the aqueous phase is a salt solution, and the concentration of the salt solution is 1-10%.

[0015] The present application also provides a quantum dot diffusion plate, comprising the quantum dot composite as described above.

[0016] The present application also provides a method for preparing a quantum dot diffusion plate, comprising the steps of:

[0017] Providing a precursor, the precursor comprising the quantum dot complex prepared by the method described above, and a host polymer;

[0018] The step of mixing the precursors at a temperature at or above the melting point of the host polymer and then cooling.

[0019] The present application also provides a light-emitting device, comprising the quantum dot diffusion plate as described above.

[0020] Beneficial effects: The quantum dot composite of the present application includes a solid shell and a liquid core, wherein the liquid core contains quantum dots, a photoinitiator, and a prepolymer, and the solid shell is formed by photocuring the liquid core. Since the refractive index of the solid shell of the quantum dot composite is inconsistent with that of the liquid core, the light conversion efficiency of the overall quantum dot composite is improved. The quantum dot composite is evenly dispersed in the main layer, which can effectively improve the light conversion rate and light output brightness of the obtained quantum dot diffusion plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the structure of the quantum dot complex in the first specific embodiment of the present application;

[0022] Figure 2 This is a schematic diagram of the structure of a quantum dot diffusion plate in the first specific implementation mode of the present application;

[0023] Figure 3 This is a schematic diagram of the structure of a quantum dot diffusion plate in the fifth specific implementation manner of the present application;

[0024] Figure 4 It is a schematic diagram of the structure of a quantum dot diffusion plate in the seventh specific implementation manner of the present application. DETAILED DESCRIPTION

[0025] The following will describe the technical solutions in the embodiments of the present application in detail in combination with the embodiments of the present application. It should be noted that the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0026] The terms used herein are only used to describe the purpose of specific embodiments and are not intended to be restrictive. If not defined otherwise, all terms (including technical and scientific terms) in the specification may be defined as those skilled in the art generally understand. The terms defined in the common dictionary should be interpreted as having the meaning consistent with their background in the relevant field and the meaning in the present disclosure, and cannot be interpreted in an ideal manner or too broadly, unless clearly defined. In addition, unless clearly described to the contrary, the wording "including" and the wording "comprising" indicate the presence of stated features, regions, wholes, steps, operations, elements, and / or components when used in this specification, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their sets. Therefore, the above wording will be understood to mean including stated elements, but do not exclude any other elements.

[0027] It will be understood that although the terms first, second, etc. can be used in this article to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish an element, component, region, layer or part from another element, component, region, layer or part. Thus, without departing from the teaching of the present embodiment, the first element, component, region, layer or part discussed below can be referred to as the second element, component, region, layer or part.

[0028] definition

[0029] The following definitions apply to some aspects described with respect to some embodiments of the present invention, and these definitions may also be expanded herein.

[0030] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Reference to an item may include plural items unless the context clearly dictates otherwise.

[0031] As used herein, the term "adjacent" refers to being close to or adjacent to each other. Adjacent objects may be spaced apart from each other, or may be in actual or direct contact with each other. In some cases, adjacent objects may be connected to each other, or may be integrally formed with each other.

[0032] As used herein, the term "connected" refers to an operational coupling or link. Linked objects can be directly coupled to each other, or can be indirectly coupled to each other via another set of objects.

[0033] As used herein, relative terms such as "inside", "inner", "outside", "exterior", "top", "bottom", "front", "back", "rear", "upper", "lower", "vertical", "lateral", "above", and "below" refer to the orientation of a group of objects relative to each other, for example according to a drawing, but no specific orientation of these objects is required during manufacturing or use.

[0034] like Figure 1 , which is a schematic diagram of the structure of a quantum dot complex in the first specific embodiment of the present application, wherein the quantum dot complex 10 comprises a solid shell 11 and a liquid core 12, wherein the liquid core 12 comprises quantum dots, a photoinitiator, and a prepolymer, and the solid shell 11 is formed by photocuring the liquid core 12. The solid shell 11 and the liquid core 12 have different refractive indices and both contain quantum dots. When the quantum dot complex 10 is used to prepare a quantum dot light diffuser plate, the light conversion efficiency of the quantum dot diffuser plate can be enhanced.

[0035] In the second specific embodiment of the present application, the particle size of the quantum dot complex is 0.1-1000 μm, and the inner diameter of the liquid core is 0.04-500 μm, thereby improving the light conversion efficiency of the quantum dot complex.

[0036] In the third specific embodiment of the present application, the prepolymer includes at least one of aliphatic polyurethane acrylate oligomers, aromatic polyurethane acrylate oligomers, epoxy oligomers, and polyester acrylate oligomers, and such prepolymers can be photocured under certain conditions.

[0037] In the fourth specific embodiment of the present application, the liquid core contains the following components: the weight percentage of quantum dots is 1 to 30wt%, the weight percentage of photoinitiator is 0.1 to 10wt%, the weight percentage of prepolymer is 10 to 80wt%, and the weight percentage of monomer is 0 to 50wt%, thereby obtaining a quantum dot complex with excellent light conversion performance.

[0038] The present application also provides a method for preparing a quantum dot composite, comprising the steps of:

[0039] S1, mixing quantum dots, photoinitiator, and prepolymer to form a quantum dot glue solution;

[0040] S2, adding the quantum dot glue solution into an aqueous phase with a pH value of 7 to 9, and irradiating with ultraviolet light to obtain the quantum dot complex.

[0041] The viscosity of the quantum dot colloid solution is 500-30000 cp, which can enable the quantum dot colloid solution to better form a quantum dot complex in the water phase.

[0042] The aqueous phase of the present application can be selected from a salt solution, which can be a salt solution containing alkaline earth metal ions, such as sodium chloride solution, sodium sulfate solution, magnesium chloride solution, magnesium sulfate solution, magnesium nitrate solution, sodium nitrate solution, potassium sulfate solution, potassium chloride solution, potassium nitrate solution or buffer solution, so that the quantum dot colloid solution can form a quantum dot complex well in the aqueous phase.

[0043] Preferably, the aqueous phase contains a salt solution, and the concentration of the salt solution is 1-10%, so that the quantum dot complex is evenly suspended and dispersed in the aqueous phase.

[0044] Furthermore, step S2 includes: using an atomizing device to spray the quantum dot glue solution into the water phase.

[0045] For example, the pressure of the atomizing device can be adjusted to spray the quantum dot glue solution into the water phase.

[0046] Furthermore, the wavelength of the ultraviolet light is 365-395nm, and the energy is 1000-20000mJ / cm 2 , so that the quantum dot complex forms a liquid core and a solid shell.

[0047] It can be understood that the quantum dot composites in the present application are generally spherical, and at room temperature and pressure, the liquid core is in a flowable state, and the liquid core can be, for example, in a molten state or a gel state, and the solid shell is in a solidified state; the organic high molecular polymer contained in the solid shell is solidified from the prepolymer in the liquid core.

[0048] The present application also provides a method for preparing a quantum dot diffusion plate, such as Figure 2 As shown, the quantum dot diffusion plate 100 includes a main layer 100 and a quantum dot complex 10, and a plurality of the quantum dot complexes 10 are distributed in the main layer 100; Figure 2 As shown, the quantum dot composite is integrated into the main layer of the diffuser plate, which can effectively reduce the thickness of the backlight module and improve the light conversion efficiency of the quantum dot diffuser plate.

[0049] The present application also provides a method for preparing a quantum dot diffusion plate, comprising the steps of:

[0050] Providing a precursor, the precursor comprising the quantum dot complex as described above, and a host polymer;

[0051] The step of mixing the precursors at a temperature at or above the melting point of the host polymer and then cooling.

[0052] The main polymer in the present application is used to form the main layer. In the quantum dot composite, the polymer in the solid shell will be in an insoluble and non-melting state at a temperature at or above the melting point of the main polymer, and the quantum dot composite will be dispersed in the main layer.

[0053] Furthermore, in the quantum dot diffusion plate, the weight percentage of the quantum dot composite is 0.01-20 wt %, so that the light has more transmission paths in the main layer.

[0054] In a preferred embodiment, in the quantum dot composite, the weight percentage of quantum dots is 1 to 10 wt %, thereby improving the light conversion efficiency of the quantum dot composite and further enhancing the luminous brightness of the quantum dot diffusion plate.

[0055] Furthermore, the quantum dot diffuser plate includes a light incident surface and a light emitting surface. In the direction from the light incident surface to the light emitting surface, the amount of quantum dot complexes in the main layer gradually decreases, further increasing the light conversion efficiency of the quantum dot diffuser plate.

[0056] Furthermore, if Figure 3 As shown, the quantum dot diffusion plate 1 includes a first protective layer 200, a main layer 100, and a second protective layer 300 which are stacked in sequence. The first protective layer 200, the main layer 100, and the second protective layer 300 are integrally formed. The first protective layer 200 and the second protective layer 300 can protect the quantum dots in the main layer 100 from water and oxygen invasion. The integral forming can, for example, prepare the quantum dot diffusion plate by co-extrusion of more layers. Compared with the existing coating liquid that is UV-cured to prepare a sandwich-structured quantum dot film, the preparation method of the present application can be cooled and cured once, does not require the use of an ultraviolet light source for curing, and the thickness of each layer in the quantum dot diffusion plate 1 is easy to control.

[0057] In a preferred embodiment, the protective layer and the main layer are both made of a light-transmitting material, and the material of the protective layer includes an inorganic material and / or an organic coating, wherein the inorganic material is, for example, at least one of aluminum oxide, aluminum nitride, aluminum oxynitride, titanium oxide, titanium nitride, titanium oxynitride, zirconium oxide, zirconium nitride, zirconium oxynitride, silicon oxide, silicon carbide, silicon oxynitride, and graphene, and the organic coating includes polysilicone, polyepoxy, polyurethane, polycarbonate, polyfluororesin, polymethyl methacrylate, polyoxymethylene, polyethylene, polyvinylidene chloride, ethylene- At least one of vinyl alcohol copolymer, polyvinyl acetate, polytetrafluoroethylene, polyvinyl butyral, polypropylene, polyamide, polyethylene terephthalate, polyethylene naphthalate, or polybutylene terephthalate, polyacrylate, polystyrene acrylonitrile resin, poly Columbia resin, poly CR-39 resin, poly OZ series resin, poly TS-26 resin, poly APO resin, poly MR resin, poly MH resin, poly NAS resin, poly ADC resin, poly TOPAS resin, and poly ARTON resin.

[0058] Furthermore, the thickness of the main layer is 100-2000 μm, thereby ensuring that the quantum dot diffuser plate obtains excellent light transmittance and light conversion efficiency.

[0059] Furthermore, the main polymer is at least one of polystyrene, polyethylene, polypropylene, polythioene, polyurethane, polymethyl methacrylate, and polymethyl methacrylate-styrene copolymer, so as to facilitate the preparation of the quantum dot diffusion plate by an extrusion process.

[0060] In the seventh specific implementation of the present application, Figure 4 As shown, the main layer in the quantum dot diffusion plate 1 includes a first main layer 101 and a second main layer 102 which are stacked, and the quantum dot complex includes a red light quantum dot complex and a green light quantum dot complex. A plurality of red light quantum dot complexes are distributed in the first main layer 101, and a plurality of green light quantum dot complexes are distributed in the second main layer 102 to avoid self-absorption caused by mixing different quantum dots. The first main layer 101 and the second main layer 102 are prepared by co-extrusion and are integrally formed.

[0061] The green light quantum dots and the red light quantum dots include one of silicon-based quantum dots, IIB-VIA group compound quantum dots, IIIA-VA group compound quantum dots, VA-VIA group compound quantum dots, perovskite quantum dots and a mixture of the above various quantum dots. The IIB-VIA group compound quantum dots include one selected from the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IIIA-VA group compound quantum dots include one selected from the group consisting of GaN, GaP, GaAs, AlN, AlP, AlAs, InN, InP, InAs, GaNP, GaNAs, GaPAs, AlNP, AlNAs, AlPAs, InNP, InNAs, InPAs, GaAlNP, GaAlNAs, GaAlPAs, GaInNP, GaInNAs, GaInPAs, InAlNP, InAlNAs and InAlPAs. In a preferred embodiment, the quantum dots are core-shell structures. In a preferred embodiment, the green light quantum dots and the red light quantum dots include at least one of the following substances: cadmium selenide, cadmium sulfide, cadmium telluride, zinc selenide, indium phosphide, indium arsenide, perovskite.

[0062] Furthermore, the quantum dot diffuser plate also includes light diffusion particles, which are dispersed in the main layer to further enhance the light extraction efficiency. The particle size of the light diffusion particles is 100nm~5μm. In the quantum dot diffuser plate, the weight percentage of the light diffusion particles is 0.1~10wt%, and the light diffusion particle material is at least one of silicone, PMMA, PS, nano silicon oxide, nano aluminum oxide, nano titanium oxide, and nano zirconium oxide.

[0063] The present application also provides a light-emitting device, including the above-mentioned quantum dot diffusion plate, the light-emitting device can be a display device, or a lighting device, the display device includes but is not limited to mobile phones, computers, car displays, AR displays, VR displays, smart watches, flexible display screens, flexible display panels and other devices. The light-emitting device of the present application can be a top light-emitting device, a bottom light-emitting device, or a transparent light-emitting device.

[0064] The structure of a display device according to some exemplary embodiments of the present application will be described in more detail below; however, the exemplary embodiments of the present application are not limited thereto.

[0065] Example (1-1)

[0066] Step 1: Prepare quantum dot glue solution. The concentrations of the following components refer to the mass concentrations in the quantum dot glue solution:

[0067] (1) Green light CdSe / ZnS quantum dot glue solution: Aromatic polyurethane acrylate CN9167 purchased from Sartomer with a mass concentration of 55.5wt%, 30wt% of dicyclopentadiene methacrylate CD535, 3wt% of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), and 0.5wt% of 2-isopropylthioxanthone were mixed, and then 1wt% of titanium dioxide and 10wt% of green light CdSe / ZnS quantum dots were added in sequence and mixed evenly to obtain a green light quantum dot glue solution.

[0068] (2) Red light CdSe / ZnS quantum dot glue solution: Aromatic polyurethane acrylate CN9167 purchased from Sartomer with a mass concentration of 55.5wt%, pentaerythritol tetraacrylate SR295 NS with a mass concentration of 30wt%, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 0.5wt% 2-isopropylthioxanthone were mixed, and then 1wt% titanium dioxide and 10wt% red light CdSe / ZnS quantum dots were added in sequence and mixed evenly to obtain a red light quantum dot glue solution.

[0069] Step 2: Preparation of quantum dot complexes:

[0070] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 1μm, wherein the inner diameter of the liquid core was 500nm.

[0071] (2) Red light quantum dot complex: After the red light quantum dot glue liquid is sprayed into water using an atomizer, it is irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 1μm, in which the inner diameter of the liquid core is 500nm.

[0072] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0073] According to the mass percentage of each component in the diffuser plate, 5wt% of green light quantum dot complex, 1wt% of red light quantum dot complex, 89wt% of polystyrene and 5wt% of silicone light diffuser are blended and extruded at 210°C to form a CdSe / ZnS quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0074] Example (1-2)

[0075] Step 1: The steps for preparing the quantum dot glue solution are roughly the same as those in Example (1-1).

[0076] Step 2: Preparation of quantum dot complexes:

[0077] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 5μm, wherein the inner diameter of the liquid core was 3μm.

[0078] (2) Red light quantum dot complex: After the red light quantum dot glue liquid was sprayed into water using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 5μm, wherein the inner diameter of the liquid core was 2.5μm.

[0079] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0080] According to the mass percentage of each component in the diffuser plate, 10wt% of green light quantum dot complex, 2wt% of red light quantum dot complex, 83wt% of polystyrene and 5wt% of silicone light diffuser are blended and extruded at 210°C to form a CdSe / ZnS quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0081] Embodiment (1-3)

[0082] Step 1: The steps for preparing the quantum dot glue solution are roughly the same as those in Example (1-1).

[0083] Step 2: Preparation of quantum dot complexes:

[0084] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 10μm, wherein the inner diameter of the liquid core was 8μm.

[0085] (2) Red light quantum dot complex: After the red light quantum dot glue liquid is sprayed into water using an atomizer, it is irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 10μm, in which the inner diameter of the liquid core is 8μm.

[0086] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0087] According to the mass percentage of each component in the diffuser plate, 20wt% of green light quantum dot complex, 4wt% of red light quantum dot complex, 71wt% of polystyrene and 5wt% of silicone light diffuser are blended and extruded at 210°C to form a CdSe / ZnS quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0088] Example (2-1)

[0089] Step 1: Prepare quantum dot glue solution. The concentrations of the following components refer to the mass concentrations in the quantum dot glue solution:

[0090] (1) Green light quantum dot solution: Aromatic polyurethane acrylate CN970A60NS purchased from Sartomer with a mass concentration of 55.5wt%, 20wt% tricyclohexane dimethanol diacrylate SR833NS, 3wt% 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), and 0.5wt% 2-isopropylthioxanthone were mixed, and then 1wt% titanium dioxide and 20wt% green light InP / ZnS quantum dots were added in sequence and mixed evenly to obtain a green light quantum dot solution.

[0091] (2) Red light quantum dot solution: Aromatic polyurethane acrylate CN970A60NS purchased from Sartomer with a mass concentration of 55.5wt%, tricyclohexane dimethanol diacrylate SR833NS with a mass concentration of 20wt%, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) with a mass concentration of 3wt% and 2-isopropylthioxanthone with a mass concentration of 0.5wt% were mixed, and then 1wt% of titanium dioxide and 20wt% of red light InP / ZnS quantum dots were added in sequence and mixed evenly to obtain a red light quantum dot solution.

[0092] Step 2: Preparation of quantum dot complexes:

[0093] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 1μm, wherein the inner diameter of the liquid core was 500nm.

[0094] (2) Red light quantum dot complex: After the red light quantum dot glue liquid is sprayed into water using an atomizer, it is irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 1μm, in which the inner diameter of the liquid core is 500nm.

[0095] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0096] According to the mass percentage of each component in the diffuser plate, 10wt% of green light quantum dot complex, 2wt% of red light quantum dot complex, 83wt% of polystyrene and 5wt% of silicone light diffuser are blended and extruded at 210°C to form an InP / ZnS quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0097] Example (2-2)

[0098] Step 1: The steps for preparing the quantum dot glue solution are roughly the same as those in Example (2-1).

[0099] Step 2: Preparation of quantum dot complexes:

[0100] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 5μm, wherein the inner diameter of the liquid core was 3μm.

[0101] (2) Red light quantum dot complex: After the red light quantum dot glue liquid was sprayed into water using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 5μm, wherein the inner diameter of the liquid core was 2.5μm.

[0102] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0103] According to the mass percentage of each component in the diffuser plate, 20wt% of green light quantum dot complex, 4wt% of red light quantum dot complex, 71wt% of polystyrene and 5wt% of silicone light diffuser were blended and extruded at 210°C to form an InP / ZnS quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0104] Example (2-3)

[0105] Step 1: The steps for preparing the quantum dot glue solution are roughly the same as those in Example (2-1).

[0106] Step 2: Preparation of quantum dot complexes:

[0107] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 10μm, wherein the inner diameter of the liquid core was 8μm.

[0108] (2) Red light quantum dot complex: After the red light quantum dot glue liquid is sprayed into water using an atomizer, it is irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 10μm, in which the inner diameter of the liquid core is 8μm.

[0109] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0110] According to the mass percentage of each component in the diffuser plate, 20wt% of green light quantum dot complex, 4wt% of red light quantum dot complex, 71wt% of polystyrene and 5wt% of silicone light diffuser were blended and extruded at 210°C to form an InP / ZnS quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0111] Example (3-1)

[0112] Step 1: Prepare quantum dot glue solution. The concentrations of the following components refer to the mass concentrations in the quantum dot glue solution:

[0113] (1) Green light quantum dot glue solution: 55.5wt% of aliphatic polyurethane acrylate CN985B88 purchased from Sartomer, 33wt% of tris(2-hydroxyethyl)isocyanurate triacrylate SR368D NS, 3wt% of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), and 0.5wt% of 2-isopropylthioxanthone were mixed, and then 1wt% of titanium dioxide and 8wt% of green light PVK quantum dots were added in sequence and mixed evenly to obtain a green light quantum dot glue solution.

[0114] (2) Red light quantum dot glue solution: 55.5wt% of aliphatic polyurethane acrylate CN985B88 purchased from Sartomer, 33wt% of tris(2-hydroxyethyl)isocyanurate triacrylate SR368D NS, 3wt% of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), and 0.5wt% of 2-isopropylthioxanthone were mixed, and then 1wt% of titanium dioxide and 8wt% of red light PVK quantum dots were added in sequence and mixed evenly to obtain a red light quantum dot glue solution.

[0115] Step 2: Preparation of quantum dot complexes:

[0116] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 1μm, wherein the inner diameter of the liquid core was 500nm.

[0117] (2) Red light quantum dot complex: After the red light quantum dot glue liquid is sprayed into water using an atomizer, it is irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 1μm, in which the inner diameter of the liquid core is 500nm.

[0118] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0119] According to the mass percentage of each component in the diffuser plate, 4wt% of green light quantum dot complex, 0.8wt% of red light quantum dot complex, 90.2wt% of polystyrene, and 5wt% of silicone light diffuser are blended and extruded at 210°C to form a PVK quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0120] Example (3-2)

[0121] Step 1: The steps for preparing the quantum dot glue solution are roughly the same as those in Example (3-1).

[0122] Step 2: Preparation of quantum dot complexes:

[0123] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 5μm, wherein the inner diameter of the liquid core was 3μm.

[0124] (2) Red light quantum dot complex: After the red light quantum dot glue liquid was sprayed into water using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 5μm, wherein the inner diameter of the liquid core was 2.5μm.

[0125] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0126] According to the mass percentage of each component in the diffuser plate, 8wt% of green light quantum dot complex, 2wt% of red light quantum dot complex, 85wt% of polystyrene and 5wt% of silicone light diffuser are blended and extruded at 210°C to form a PVK quantum dot complex extruded diffuser plate with a thickness of 1.0 mm.

[0127] Example (3-3)

[0128] Step 1: The steps for preparing the quantum dot glue solution are roughly the same as those in Example (3-1).

[0129] Step 2: Preparation of quantum dot complexes:

[0130] (1) Green quantum dot composite: After the green quantum dot glue liquid was sprayed into 1% sodium chloride saline using an atomizer, it was irradiated with 365nm ultraviolet light to obtain a green quantum dot composite with a particle size of 10μm, wherein the inner diameter of the liquid core was 8μm.

[0131] (2) Red light quantum dot complex: After the red light quantum dot glue liquid is sprayed into water using an atomizer, it is irradiated with 365nm ultraviolet light to obtain a red light quantum dot complex with a particle size of 10μm, in which the inner diameter of the liquid core is 8μm.

[0132] Step 3: Preparation of quantum dot composite extrusion diffusion plate:

[0133] According to the mass percentage of each component in the diffuser plate, 15wt% of green light quantum dot complex, 3wt% of red light quantum dot complex, 72wt% of polystyrene, and 5wt% of silicone light diffuser are blended and extruded at 210°C to form a PVK quantum dot complex extruded diffuser plate with a thickness of 1.0mm.

[0134] Comparative Example 1

[0135] Preparation of quantum dot diffuser plate:

[0136] According to the mass percentage of each component in the diffuser plate, 0.15wt% of green light CdSe / ZnS quantum dots, 0.01wt% of red light CdSe / ZnS quantum dots, 94.84wt% of polystyrene, and 5wt% of silicone light diffuser were blended and extruded at 210°C to form a quantum dot diffuser plate with a thickness of 1.0mm.

[0137] Comparative Example 2

[0138] According to the mass percentage of each component in the diffuser plate, 0.6wt% of green light InP / ZnS quantum dots, 0.04wt% of red light InP / ZnS quantum dots, 94.36wt% of polystyrene, and 5wt% of silicone light diffuser were blended and extruded at 210°C to form a quantum dot diffuser plate with a thickness of 1.0mm.

[0139] Comparative Example 3

[0140] According to the mass percentage of each component in the diffuser plate, 0.01wt% of green light PVK quantum dots, 0.01wt% of red light PVK quantum dots, 94.98wt% of polystyrene, and 5wt% of silicone light diffuser were blended and extruded at 210°C to form a quantum dot diffuser plate with a thickness of 1.0mm.

[0141] The quantum dot diffusion plates in the embodiments and comparative examples were irradiated with blue light having a wavelength of 450 nm and a brightness of 1000 nits, and the optical properties of the quantum dot diffusion plates were measured. The specific results are shown in Table 1.

[0142] Table 1 Optical performance parameters of quantum dot diffusion plates in Examples and Comparative Examples

[0143] serial number Brightness of light Light conversion efficiency Example (1-1) 3870nits 387% Example (1-2) 6218nits 621% Embodiment (1-3) 9321nits 932% Example (2-1) 2034nits 203% Example (2-2) 3547nits 354% Example (2-3) 4169nits 416% Example (3-1) 3689nits 368% Example (3-2) 4529nits 452% Example (3-3) 5923nits 592% Comparative Example 1 2781nits 278% Comparative Example 2 1204nits 120% Comparative Example 3 2134nits 213%

[0144] It can be seen from Table 1 that the quantum dot diffuser plate in the embodiment of the present application has higher luminous brightness and better light conversion efficiency than the ordinary quantum dot diffuser plate in the comparative example.

[0145] Although the inventors have elaborated and enumerated the technical solutions of the present application in detail, it should be understood that it is obvious for those skilled in the art to modify and / or adapt the above embodiments or adopt equivalent alternative solutions, which cannot deviate from the essence of the spirit of the present application. The terms appearing in the present application are used to explain and understand the technical solutions of the present application and cannot constitute limitations on the present application.

Claims

1. A quantum dot composite, characterized in that: It comprises a solid shell and a liquid core, wherein the liquid core comprises a quantum dot glue liquid, wherein the quantum dot glue liquid comprises quantum dots, a photoinitiator and a prepolymer, and the solid shell is formed by photocuring the quantum dot glue liquid; the prepolymer comprises at least one of aliphatic polyurethane acrylate oligomer, aromatic polyurethane acrylate oligomer, epoxy oligomer and polyester acrylate oligomer; the particle size of the quantum dot complex is 0.1-1000 μm, and the inner diameter of the liquid core is 0.04-500 μm.

2. The quantum dot composite according to claim 1, characterized in that The liquid core contains the following components: the weight percentage of the quantum dots is 1-30 wt %, the weight percentage of the photoinitiator is 0.1-10 wt %, the weight percentage of the prepolymer is 10-80 wt %, and the weight percentage of the monomer is 0-50 wt %.

3. A method for preparing a quantum dot composite as claimed in any one of claims 1 to 2, characterized in that: Includes steps: S1, mixing quantum dots, photoinitiator, and prepolymer to form a quantum dot glue solution; S2, adding the quantum dot glue liquid into an aqueous phase with a pH value of 7-9, and obtaining the quantum dot complex after irradiation with ultraviolet light; and spraying the quantum dot glue liquid into the aqueous phase using an atomizing device.

4. The method for preparing the quantum dot composite according to claim 3, characterized in that: The aqueous phase comprises a salt solution, and the mass percentage concentration of the salt solution is 1-10%.

5. A quantum dot diffusion plate, characterized in that: It includes a quantum dot complex prepared by the method described in any one of claims 1 to 2 or any one of claims 3 to 4.

6. A method for preparing a quantum dot diffusion plate, characterized in that: Includes steps: Providing a precursor, the precursor comprising a quantum dot complex prepared by the method of any one of claims 1 to 2 or any one of claims 3 to 4, and a host polymer; The step of mixing the precursors at a temperature at or above the melting point of the host polymer and then cooling.

7. A light emitting device, characterized in that: A quantum dot diffusion plate comprising the method described in claim 5 or prepared by the method described in claim 6.

Citation Information

Patent Citations

  • Method for preparing white fluorescent quantum dot composite particles by microfluid method

    CN103710017A

  • White quantum dot composite particle as well as preparation method and device thereof

    CN103788270A